Sweetpotato for Health and Wealth in Nigeria Underway - Phorbee, O.; Udossen, J. (International Potato Center, 2015)
This flyer provides details about the objectives, activities, achievements and the future plans of the ‘Sweetpotato for Health and Wealth’ in Nigeria project. The project plans to establish committed Decentralized Vine Multipliers (DVMs) to increase access to quality vines to at least 17,500 households by 2019 in Nassarawa, Benue, Ebonyi, Kaduna, Kwara, and Osun states, especially those with children below five years of age and women of reproductive age.